#TITLE_ALTERNATIVE# - NUGROHO (NIM 23206308), AGUS
On an air combat simulation computer based, human player who's involved as a user will be positioned against a plane. The plane on that simulator called a computer artificial intelligence. Therefore, a scenario must be designed to place the human being to fight against the computer as their enemy. And the computer must be designed automatically to fight based on human being intelligence. The background of this Thesis is the importance of creating a prototype that could think and act based on character and the ability of human intelligence (Intelligent Agent pilot). This Thesis is focusing on how to represent the movement of an air craft pilot agent along with the movement combination that results another movement on an air combat mission (dogfight air combat). Simulation model for the air craft movement is designed to predict the movement of an air craft along with the requirements. The research evaluation result of this Thesis shows a trajectlist graphic of the pilot agent air movement ability on interacting with its environment. Pilot agent is able to move straight, turn left, and turn right for 450 and 900. It also able to perform immelmann maneuver, 3600 loop maneuver, pitch up, pitch down, and move straight up or straight down for 450. All of this movement requires a calculated distance on a rule-based moving design. As a conclusion, the ability and performance of an air craft is a reaction which is depend on the action of all moving elements in the air.